2005
DOI: 10.1021/bm050260e
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Effects of Shell Cross-Linked Nanoparticle Size, Core Composition, and Surface PEGylation on in Vivo Biodistribution

Abstract: Amphiphilic core-shell nanoparticles have drawn considerable interest in biomedical applications. The precise control over their physicochemical parameters and the ability to attach various ligands within specific domains suggest shell cross-linked (SCK) nanoparticles may be used as multi-/polyvalent scaffolds for drug delivery. In this study, the biodistribution of four SCKs, differing in size, core composition, and surface PEGylation, was evaluated. To facilitate in-vivo tracking of the SCKs, the positron-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
192
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(197 citation statements)
references
References 63 publications
4
192
1
Order By: Relevance
“…The biodistribution of 14 C-labeled NP 9 30 min after administration revealed that NPs accumulated mainly in the liver and kidney (Fig. 4C), indicating that the NPs were recognized by macrophages in the liver similar to the fate of other nano objects of similar size (11)(12)(13)(14).…”
Section: Stability Of Nps In Plasmamentioning
confidence: 84%
See 1 more Smart Citation
“…The biodistribution of 14 C-labeled NP 9 30 min after administration revealed that NPs accumulated mainly in the liver and kidney (Fig. 4C), indicating that the NPs were recognized by macrophages in the liver similar to the fate of other nano objects of similar size (11)(12)(13)(14).…”
Section: Stability Of Nps In Plasmamentioning
confidence: 84%
“…It has been reported that the NPs smaller than approximately 8 nm will be cleared rapidly from the blood stream by the renal system and NPs larger than 200 nm will be sequestered by the mononuclear phagocytic system (MRS) in the liver and spleen (11)(12)(13)(14). Hydrophobicity, charge, flexibility, and shape of NPs are also important; for example hydrophobic particles induce formation of a corona of serum proteins around the surface and strongly charged NPs will be phagocytosed by MRS faster than neutral particles (11)(12)(13)(14)(15)(16)(17)(18). Although the size of NPs can be adjusted, surface charges and hydrophobicity of plastic antidotes cannot always be optimized to increase circulation time since surface functionality must be designed to maximize affinity and capacity to target molecules.…”
mentioning
confidence: 99%
“…48 Furthermore, because of its half-life (12.7 h), 64 Cu was recently used to evaluate the in vivo distribution and targeting capabilities of polymeric nanoparticles functionalized with tetraazamacrocyclic chelators. 33,[49][50][51] Herein, we report the synthesis, via NMP, of a series of welldefined, functionalized PEGylated star-shaped copolymers containing a core-shell morphology with DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) functional groups in the inner shell, which are available for 64 Cu-labeling while at the same time being screened by an outer PEG shell. Within this body of work, star-like copolymers and the linear arm copolymers used to generate them are evaluated in vivo by means of biodistribution experiments and small animal PET imaging.…”
Section: Introductionmentioning
confidence: 99%
“…As a general rule, however, a ratio of hydrophilic block to total polymer mass of approximately ≀35% ± 10% yields membrane structures, while copolymers with ratios greater than 45% generally form micelles; those with ratios less than 25% form inverted microstructures [14]. Micellar structures have been used as intracellular and systemic delivery systems [15][16][17][18] but present significant limitations when compared to polymersomes. In aqueous solutions, they can only encapsulate hydrophobic molecules unless strong binding or covalent linking strategies are incorporated for sequestering aqueous-soluble components.…”
Section: Introductionmentioning
confidence: 99%